Photodynamic therapy of tumors with pyropheophorbide-a-loaded polyethylene glycol–poly(lactic-co-glycolic acid) nanoparticles - Liu H (Dove Medical Press, 2016)
Hui Liu,1 Mei Zhao,1 Jin Wang,1 Mingpei Pang,1 Zhenzhou Wu,1 Liqing Zhao,1 Zhinan Yin,1,2 Zhangyong Hong1 1State Key Laboratory of Medicinal Chemical Biology, College of Life Sciences, Nankai University, Tianjin, 2Biomedical Translational Research Institute, International Immunology Center, Jinan University, Guangzhou, People’s Republic of China Abstract: Photodynamic therapy (PDT) has many advantages in treating cancers, but the lack of ideal photosensitizers continues to be a major limitation restricting the clinical utility of PDT. This study aimed to overcome this obstacle by generating pyropheophorbide-a-loaded polyethylene glycol–poly(lactic-co-glycolic acid) nanoparticles (NPs) for efficient tumor-targeted PDT. The fabricated NPs were efficiently internalized in the mitochondrion by cancer cells, and they efficiently killed cancer cells in a dose-dependent manner when activated with light. Systemically delivered NPs were highly enriched in tumor sites, and completely ablated the tumors in a xenograft KB tumor mouse model when illuminated with 680 nm light (156 mW/cm2, 10 minutes). The results suggested that this tumor-specific NP-delivery system for pyropheophorbide-a has the potential to be used in tumor-targeted PDT. Keywords: photodynamic therapy, photosensitizer, pyropheophorbide-a, nanoparticle